Red Mullet (Mullus barbatus) Collected from North and South Euboean Gulf, Greece: Fishing Location Effect on Nutritive Quality - Roxana-Georgiana Nita; Vassilis Athanasiadis; Dimitrios Kalompatsios; Martha Mantiniotou; Aggeliki Alibade; Chrysanthi Salakidou; Stavros I. Lalas (Fishes)
Red mullet (Mullus barbatus), a prominent fish species in the Mediterranean Sea, is a fish with a particular abundance of unsaturated fatty acids and other nutrients, including a substantial quantity of minerals. The nutritive quality parameters (lipid quality indices, fatty acid profiles, and mineral content, along with proximate composition) of 75 red mullet samples collected from five distinct locations (L1–L5) in the North and South Euboean Gulf, Euboea Island (Evia), Greece, were examined. It was hypothesized that the different habitats may have an impact on each fish’s chemical composition. Proximate composition (protein, ash, moisture, fat, and minerals) and bioactive compound determination (total carotenoids, and vitamins A, E, and C) were conducted on the lyophilized fish samples. The protein and lipid content of the wet fillet varied substantially from 10.8 to 14.3 and 13.2 to 16.8% w/w, respectively. The samples exhibited statistically non-significant variation in the total SFAs and MUFAs (p > 0.05). The level of total PUFAs was above 30% in all the samples and no significant differences were observed between them. However, arachidonic acid (20:4 ω-6) was only detected in fish samples from two locations (i.e., L1 and L3). The concentrations of Fe, Na, Mg, K, Ca, Ag, Sr, Li, and Zn varied significantly (p < 0.05) in relation to the size of the fish samples. The highest concentrations of heavy metals were detected at the northern location (L5), indicating a possible negative correlation between size and arsenic concentration. The varied mineral composition and fatty acid content of the samples can be attributed to their distinctive biological characteristics (i.e., length and weight) and dietary environments.